Meditate to create: mindfulness and creativity in an arts and design learning context - Henriksen, Danah; Heywood, William; Gruber, Natalie (Creativity Studies, 2022)
Given the applied nature of creativity in the arts and design, it is important to understand the conditions and practices that support it. Most research suggests that ideal conditions for creativity are often mental and emotional – involving relaxed, yet alert and focused, states of mind. This article explores the connection between mindfulness and creativity in the experiences of students in a college of arts and design, through a mindfulness teaching practice to support creative processes. In a “scholarship of teaching and learning” inquiry, we consider how mindfulness practice may affect arts and design learners’ feelings about their own creativity. Students in a large United States university school of arts and design practiced mindfulness meditation for several months, and submitted a written reflection on their experience. We qualitatively analyze this to consider how mindfulness supports creative practices in arts and design learners’ education. Our findings involve three key themes, which are: “Processing anxiety and negative feelings”, “Focusing the mind”, and “Managing the ‘Voice of Judgment’”. These thematic findings reflect how arts and design students perceive the effects of mindfulness on their creative process. We offer implications for teaching practices related to mindfulness meditation practice aimed to support learners’ perceptions of their creativity.